Etika Penawaran Jual Beli dalam Telaah Hadits Ahkam - Sukma Sari Dewi Chan (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2018)
How does Islam laid the foundations of supply ethics in buying and selling transactions? This question will be answered in this article by exploring the hadiths related to the basic principles and ethics of buying and selling in Islam. This ethic is endowed with buyers and sellers who seek to safeguard the interests and feelings of each party. These hadiths are tested using the سوم and بيع keywords then grouped according to the subject matter. These hadiths are then analyzed to gain a complete understanding of the ethical buying and selling offerings in Islam.